Property division of unmarried cohabitants in Malaysia - Buvanis Karuppiah (Penerbit Universiti Kebangsaan Malaysia, 2017)
There is no statutory framework to protect the property interests of unmarried cohabitants in Malaysia at the present time. Many couples engaged in unmarried cohabitation encounter issues relating to the division of property when a relationship breaks down, for example, because of separation or death. A cohabitant who has contributed to a lesser financial degree, but who has made significant non-financial contributions is often economically disadvantaged when the relationship ends. Whilst the Law Reform (Marriage and Divorce) Act 1976 applies to married couples in the division of matrimonial property that takes into account both financial and non-financial contributions, this statutory right is not extended to unmarried cohabitants. For cohabitants, the common law principles of resulting and constructive trusts apply. The courts adopt a “functional approach” in recognising the relationship and the manner of dividing the property. Even though case law recognises unmarried cohabitation and their rights to the division of property, a statutory recognition is essential to provide a clearer guideline that would encourage consistent judicial outcome. This would protect the interests of unmarried cohabitants in Malaysia.